The Relationship Between English Movie Watching And Students’ Speaking Skill - Ahmad Fuaidi; Muhammad Husnu; M. Iwan Abidin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this research was to study the relationship between students English watching movie-watching and students speaking ability. The research was conducted in the 11 grade of MA Nurussalam Tetebatu in academic year 2023. The researcher used correlation design method as part of quantitative research and resulted in identification of significant relationship between study and variable. The result of correlation between students in watching English movie and students' speaking ability was 0.049. It was low correlation between the students in the watching English movies and the students speaking abilities at second grade.